2018
DOI: 10.1590/1678-992x-2016-0450
|View full text |Cite
|
Sign up to set email alerts
|

Boll weevil within season and off-season activity monitored using a pheromone-and-glue reusable tube trap

Abstract: ABSTRACT:The boll weevil colonizes cotton fields as early as cotton squaring, causing significant losses due to feeding and protected development inside fruiting structures throughout crop phenology. Successful control depends on control of adults and their accurate detection when they colonize the crops. The commercial trap and boll weevil attract-and-control tubes (BWACT) are the only available tools to monitor and attract-and-kill boll weevil, despite limitation in efficacy, and insecticide in BWACT is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…The whole season monitoring showed that even though farmers adopted their control practices, such as spraying borders early in the season along with insecticide application in the total area later, boll weevil reached high density at the end of the season. A similar outcome was observed by Neves et al (2018) during the 2010/2012 and 2011/2012 seasons in the Cerrado (Rondonópolis, Mato Grosso); despite all the farmers' control practices, boll weevil was detected during the early crop stage in Rondonópolis (< 35 DAE) and resulted in large populations in these fields late in the season corroborating our results. This is likely due to colonizing weevils escaping control from treated border plus weevils not targeted at the center of the field during this early crop stages.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The whole season monitoring showed that even though farmers adopted their control practices, such as spraying borders early in the season along with insecticide application in the total area later, boll weevil reached high density at the end of the season. A similar outcome was observed by Neves et al (2018) during the 2010/2012 and 2011/2012 seasons in the Cerrado (Rondonópolis, Mato Grosso); despite all the farmers' control practices, boll weevil was detected during the early crop stage in Rondonópolis (< 35 DAE) and resulted in large populations in these fields late in the season corroborating our results. This is likely due to colonizing weevils escaping control from treated border plus weevils not targeted at the center of the field during this early crop stages.…”
Section: Discussionsupporting
confidence: 90%
“…This survey can be done by direct plant inspection or with pheromone traps. During the early stage, the pheromone traps often have greater efficacy in detecting areas infested with weevil (Neves et al 2018), helping control decisions. Proper survey data for each field will ensure a judicious decision about insecticide application either only in the field border or in whole field area promoting reduction in control cost and biological control action by conserving natural enemies (Machado et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies determined that increasing dosages of grandlure usually captures more weevils (Legget, 1980) and that the combination of the pheromone with some plant volatiles increases trap captures (Magalhäes et al, 2012(Magalhäes et al, , 2016. The relatively low late-season numbers of A. grandis grandis where colored cotton cultivars are grown with BRS Aroeira is likely because there were fewer susceptible (attractive) cultivar buds in the BRS Aroeira-associated plots (Showler, Greenberg, Scott Jr., & Robinson, 2005;Neves, Torres, Barros, & Vivan, 2018). While it is possible to capture large numbers of adult A. grandis grandis in grandlure-baited large capacity traps (Showler, 2003), trapping has not been shown to reduce adult A. grandis grandis populations in commercial cotton fields (Showler, 2009b).…”
Section: Discussionmentioning
confidence: 99%